2022
DOI: 10.1002/ange.202210184
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Selective Recognition of Dicyanoaurate(I) by a Bambusuril Macrocycle in Water

Abstract: Dicyanoaurate(I) anion, [Au(CN)2]−, plays a central role in the current industrial production of gold, as its extraction from crude ore samples represents the most money‐consuming step. Herein, we present the strongest host–guest recognition of dicyanoaurate anion using the bambusuril receptor in water, a highly competitive solvent. The micromolar stability of such a complex facilitated the up to date most efficient supramolecular stripping of dicyanoaurate from activated carbon at ambient temperature. Thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Recent studies focused on the chemistry of bambusuril and its use as an effective and selective adsorbent for anions [38,39]. Recent discoveries have revealed that bambusuril can selectively bind to [Au(CN) 2 ] − ions [40], suggesting their potential application in the gold mining industry. Additionally, it has been found that semithiobambusuril, featuring terminal thiocarbonyl groups, has a fascinating ability to form highly stable and well-ordered monolayers on gold surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies focused on the chemistry of bambusuril and its use as an effective and selective adsorbent for anions [38,39]. Recent discoveries have revealed that bambusuril can selectively bind to [Au(CN) 2 ] − ions [40], suggesting their potential application in the gold mining industry. Additionally, it has been found that semithiobambusuril, featuring terminal thiocarbonyl groups, has a fascinating ability to form highly stable and well-ordered monolayers on gold surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of bambusuril is actively developing; however, there are still many questions regarding its supramolecular properties. It is known that bambusuril possesses "host-guest" properties [40,41], but to date, the suitability of BU [6] for the synthesis and stabilization of metallic nanoparticles, particularly AgNPs, has not been investigated. Previously, AgNPs stabilized with cucurbituril [7] were obtained in an aqueous medium in the presence of NaOH at room temperature [42].…”
Section: Introductionmentioning
confidence: 99%